2013
DOI: 10.1007/s00359-013-0837-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of the coreceptor Orco in insect olfactory transduction

Abstract: Insects sense odorants with specialized odorant receptors (ORs). Each antennal olfactory receptor neuron expresses one OR with an odorant binding site together with a conserved coreceptor called Orco which does not bind odorants. Orco is necessary for localization of ORs to dendritic membranes and, thus, is essential for odorant detection. It forms a spontaneously opening cation channel, activated via phosphorylation by protein kinase C. Thereafter, Orco is also activated via cyclic adenosine monophosphate (cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 120 publications
5
111
0
Order By: Relevance
“…sensitivity, are regulated by multiple intracellular signaling cascades (Nakagawa and Vosshall, 2009;Wicher, 2015). The second messenger 3′,5′-cyclic adenosine monophosphate (cAMP) is an activating ligand for Orco channels (Wicher et al, 2008;Stengl, 2010;Stengl and Funk, 2013) and has been shown to enhance the activity of olfactory sensory neurons (OSNs) that express ORs (Olsson et al, 2011;Getahun et al, 2013). Insect OSNs possess the cellular machinery required to produce cAMP (Iourgenko and Levin, 2000;Boto et al, 2010) and disruption of this signaling cascade has been reported to affect the functional properties of OSNs (Martín et al, 2001;Gomez-Diaz et al, 2004;Deng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…sensitivity, are regulated by multiple intracellular signaling cascades (Nakagawa and Vosshall, 2009;Wicher, 2015). The second messenger 3′,5′-cyclic adenosine monophosphate (cAMP) is an activating ligand for Orco channels (Wicher et al, 2008;Stengl, 2010;Stengl and Funk, 2013) and has been shown to enhance the activity of olfactory sensory neurons (OSNs) that express ORs (Olsson et al, 2011;Getahun et al, 2013). Insect OSNs possess the cellular machinery required to produce cAMP (Iourgenko and Levin, 2000;Boto et al, 2010) and disruption of this signaling cascade has been reported to affect the functional properties of OSNs (Martín et al, 2001;Gomez-Diaz et al, 2004;Deng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…17 The requirement of Orco activation for OR sensitization was already mentioned above. 60 A possible role of Orco as pacemaker channel was discussed 80 and observed for pheromone signaling in Manduca. 58 For Drosophila, this view could not be supported.…”
Section: Role Of Orcomentioning
confidence: 98%
“…For example, in a lepidopteran, the crepuscular hawk moth, Manduca sexta , there is circadian control through octopamine (OA) over the olfactory metabotropic transduction of pheromones (Schendzielorz et al, 2015). OA could act on ORCO, which has been suggested to be a hormone-controlled pacemaker channel controlling spontaneous activity, threshold and temporal resolution of pheromone detection (Stengl, 2010; Stengl and Funk, 2013). In this species, no evidence of ORCO-based ionotropic signal transduction cascade has been found (Nolte et al, 2013, 2016).…”
Section: Functional Regulation Of Neuronal Responsementioning
confidence: 99%